Learning Regional Music Expression through PJBL Using Instagram at SMP Negeri 10 Surabaya - Lukman Susilo, Muhammad Gosa; Handaningrum, Warih (Solah, 2025)
This qualitative study examines the implementation of Project-Based Learning (PjBL) integrated with social media (Instagram) in teaching musical expression at Public Junior High School 10 Surabaya. Against the backdrop of contemporary student behavioral challenges including aggression, substance abuse, and digital overexposure the research positions arts education (mandated under Indonesian Law No. 20/2003) as a vehicle for positive expression, empathy development, and socio-emotional learning. Leveraging Surabaya’s "smart city" infrastructure, the school employs a 7-week music program where Grade 7 students master traditional Indonesian songs (e.g., "Gundul-Gundul Pacul," "Ampar-Ampar Pisang") through a structured PjBL framework: foundational rhythm/instrumental training (Sessions 1–2) transitions to collaborative ensemble projects (Sessions 3–7), culminating in digital showcases on Instagram. Data from participant observation, interviews, and document analysis reveal that this approach not only enhances technical musicianship but also fosters cultural stewardship, teamwork, and critical digital engagement. Challenges like screen-time management are acknowledged, yet the model successfully merges experiential learning, local wisdom preservation, and 21st-century skills, empowering students to reinterpret cultural heritage while navigating modern platforms responsibly.